Peran Forensik Digital dalam Mengungkap Kejahatan Siber: Tantangan Prosedural dan Kebutuhan Standardisasi di Indonesia - Gilang Rizki Aji Putra (BULETIN ADALAH, 2024)
Digital forensics is a multidisciplinary field that integrates information technology and forensic science to identify, secure, extract, and analyze digital evidence for judicial proceedings. This article examines the vital role of digital forensics in uncovering cybercrime in Indonesia, analyzing its legal foundations and identifying procedural and institutional challenges affecting its effectiveness. Using normative legal research with statutory, conceptual, and case study approaches, the study finds that digital forensics serves as a crucial mechanism for transforming volatile digital traces into admissible evidence that satisfies chain of custody requirements. The Electronic Information and Transactions Law (ITE Law) and relevant Supreme Court jurisprudence provide a legal basis for the acceptance of digital evidence. However, implementation faces significant obstacles, including fragmented procedural standards, limited expert personnel, regional disparities in laboratory infrastructure, and the absence of uniform national guidelines. The article concludes that strengthening standardization, certification, and institutional capacity is essential. Keywords: Digital Forensics, Cybercrime, Chain of Custody, Electronic Information and Transactions Law (ITE Law), Digital Evidence.